Temporal Integrative Omics Reveals an Increase in Nondegradative Ubiquitylation during Primary Hepatocyte Dedifferentiation. (November 2020) - Jiang, Zhengyi; Sun, Zeyu; Ouyang, Xiaoxi; Zhao, Yalei; Zhou, Menghao; Wang, Baohong; Li, Qirui; Fan, Linxiao; Zhang, Sainan; Li, Lanjuan
Abstract: Primary hepatocytes (PHCs) are widely used in various fields, but the progressive deterioration of liver-specific features in vitro significantly limits their application. While the transcriptional regulation and whole cell proteome (WCP) of PHCs have been extensively studied, only a small number of studies have addressed the role of posttranslational modifications in this process. To elucidate the underlying mechanisms that induce dedifferentiation, we carried out parallel quantifications of the transcriptome, WCP, ubiquitinome, and phosphoproteome of rat PHCs after 0, 6, 12, 24, and 48 h of in vitro culture. Our data constitute a detailed proteomic analysis of dedifferentiated PHCs including 2196 proteins, 2056 ubiquitinated sites, and 4932 phosphorylated peptides. We revealed a low correlation between the transcriptome and WCP during dedifferentiation. A combined analysis of the ubiquitinome with the corresponding WCP indicated that the dedifferentiation of PHCs led to an increase in nondegradative K27 ubiquitination. Functional analysis of the altered phosphoproteins suggested a significant enrichment in ferroptosis. In all, 404 proteins with both ubiquitination and phosphorylation were identified to be involved in critical metabolic events. Furthermore, Ptbp1, Hnrpd, Hnrnpu, and Srrm2 were identified as hub genes. Taken together, our data provide new insights into proteome dynamics during PHC dedifferentiation and potential targets to inhibit the dedifferentiation process.